The response of polypyrrole–DBS electrochemical molecular motors to Na concentration: Analogies in cell biology - Samuel Beaumont; Toribio F. Otero (Electrochemistry Communications, 2019)
Conducting polymers employed as film electrodes in aqueous electrolytes can be viewed as a combination of electrochemical molecular motors, counterions and water: the material mimics the intracellular matrix of a muscle cell. The oxidation of a molecular motor promotes opposing macroscopic variations in the film, exchanging anions (swelling) or exchanging cations (contraction). The literature shows that the energy consumed by polymeric materials exchanging anions adapts to the local physicochemical conditions. Here, the effect of varying the electrolyte (NaCl) concentration on the electrochemical reactions of polypyrrole-DBS films under successive square current waves is presented. The reactions drive the exchange of cations with the electrolyte. The changes in the consumed energy, or the material potential, depend on the electrolyte concentration according to the same equations developed for materials which exchange anions. The energy consumed adapts instantaneously to new chemical conditions, thus containing quantitative information about the local chemical energy conditions. In terms of biological applications, the results could indicate that, regardless of the anion or cation, the energy of any chemical/biochemical reaction involving molecular motors includes quantitative information on the changing chemical conditions. Part of this energy may originate at the dendrite/muscle interface, the neuronal signal translating this information to the brain. However, the driving force which originates this nerve pulse remains unclear at present. Keywords: Conducting polymers, Electrochemical molecular machines, Allosteric sensors, Electrochemical bioreplication, Haptic muscles, Theoretical model